Insights from coronial recommendations for preventing natural deaths in sport and recreation in Québec, Canada - Richard, Philippe; Perron, Paul-André; Sylvain-Morneau, Jérémie; Poirier, Paul (Frontiers in Public Health, 2024)
Introduction. This descriptive retrospective study analyzed coronial recommendations for natural deaths in sport and recreation from January 2006 to December 2019 using data from the Bureau du coroner du Québec.Methods. Reports with recommendations were analyzed by sex, age group, cause of death, context, and activity. The nature of recommendations was assessed using a public health-based model. Thematic analysis was conducted following a four-phase approach in which themes developed were emphasized and further connected with existing literature.Results. Reports involving individuals aged 18-24 and reports related to ice hockey were significantly more likely to contain recommendations. Reports related to individuals ≥ 45 years old, or related to cycling or hunting had higher death frequencies. Most recommendations aligned with the public healthbased model but specifying implementation time frames was rare (11.7%). Nearly 60% of coroner's recommendations focused on automatic external defibrillator implementation, delivery and training.Discussion. Mitigation of sudden cardiac arrest risk for individuals ≥ 45 years old, timely treatment of life-threatening arrhythmias especially for activity practised in remote regions and specifying implementation time frames were identified as improvement areas. The multi-faceted approach to enhancing public access defibrillation developed by the International Liaison Committee on Resuscitation in 2022 addresses recurrent themes covered by coroners and holds the potential to inform evidence-based decision making.